BEBAN KERJA PSIKOLOGIS DAN FISIK DENGAN NASA-TLX DAN CARDIOVASCULAR LOAD (CVL) - Erni Krisnaningsih; Saleh Dwiyatno; Tedi Arlani; Ahmad Dedi Jubaedi; Dadi Cahyadi (Prodi Teknik Industri, Fakultas Teknik, 2023)
The unsafe behavior of workers causing work injuries and accidents is an important concern of the world so it is embraced by psychological and physical work measurements. The study aims to analyze the psychological and physical workload of employees in the quality control (QC) division, psychological workload measured by the National Aeronautics and Space Administration Task Load Index (NASA-TLX) method, and physical workload based on the percentage of Cardiovascular Load (% CVL) of 15 employees in the QC division. The research step was carried out by measuring psychological workload based on 5 aspects, namely: Psychological demand (MD), Physical Demand (PD), Own Performance (OP), Effort (EF) and Frustration Level (FR), weighting, rating and calculating the Weighted Workload (WWL) Value, determining the average WWL and interpretation based on the physical workload score value with CVL. Physical workload measurement is carried out by calculating the maximum pulse rate based on the pulse rate at work (DNK) and pulse rate at rest (DNI) to determine the percentage value of CVL. The results of the psychological workload score study using the NASA-TLX method, that 2 employees (13.33%) were in a low category while 11 employees (73.33%) were in the medium category, and 2 employees (13.33%) in the high category, proposed improvements with the addition of employees to reduce the psychological workload. The physical workload score value using the CVL method is less than 30% so the physical workload of employees is categorized as